Ultralate cerebral potentials as correlates of delayed pain perception: observation in a case of neurosyphilis. Issue 10 (October 1988) - Treede, R D; Meier, W; Kunze, K; Bromm, B
Abstract : Evoked cerebral potentials were investigated in a patient with neurosyphilis, who showed the symptoms of delayed pain perception in the lower limbs: a pinprick to the legs was perceived with a latency of more than one second. After stimulation with CO2 laser radiant heat pulses, evoked cerebral potentials of upper limbs were observed in a latency range comparable to those of healthy subjects, with a negative peak at 250 ms and a positive peak at 370 ms. In contrast, after application of laser stimuli to body sites with delayed pain perception, latency of the evoked potentials drastically increased with a vertex negativity at 1300 ms and a positivity at 1420 ms. Evoked potential measurements with conventional electrical stimuli did not show any difference between affected and unaffected body sites, that is, stimulation of the affected body sites did not produce pathological potentials.